2021
DOI: 10.35912/dpd.v1i1.400
|View full text |Cite
|
Sign up to set email alerts
|

Public service delivery in Uganda: a reconsideration of grand corruption

Abstract: Purpose: This review intends to ascertain and analyse available literature for the degree of corruption in the Ugandan public organisations and how they can be enhanced to get rid of corruption. Research methodology: Focussed Mapping Review and Synthesis approach were adopted to unpack corruption in public organisations. We examine obtainable literature using thematic approach. Results: The review exposes potential influence of both predisposing factors and precipitating factors in terms of socio-economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Finally, Pancasila Democracy, based on deliberation to reach consensus, is considered more suitable for the noble values of the Indonesian nation. Meanwhile, an election is a democratic instrument in the sense that there is no democracy without elections; even Manuel Kaseipo revealed that elections are a sacred ritual of all countries with democracy as a sacred ritual of all democratic countries (Mwesigwa, 2021).…”
Section: Fiqh Siyasah Democracy and Electionsmentioning
confidence: 99%
“…Finally, Pancasila Democracy, based on deliberation to reach consensus, is considered more suitable for the noble values of the Indonesian nation. Meanwhile, an election is a democratic instrument in the sense that there is no democracy without elections; even Manuel Kaseipo revealed that elections are a sacred ritual of all countries with democracy as a sacred ritual of all democratic countries (Mwesigwa, 2021).…”
Section: Fiqh Siyasah Democracy and Electionsmentioning
confidence: 99%
“…The sixth concern is that Uganda is one of the countries better known for high levels of corruption almost at every stage of the policy and in every sector. Obtainable studies suggest that corruption in Uganda has become so entrenched that the government agencies often entrusted with fighting corruption end up being caught in the very mess (Mwesigwa, 2021). Cases of the untouchables are very dominant in curtailing efforts against corruption and, in the end; the President has resorted to preaching good morals, threatening to deal with the thieves and being an active participant in anticorruption walks.…”
Section: The Triggers Of Csw In Contemporary Ugandamentioning
confidence: 99%
“…In spite of that provision backed by a broad legal and policy context, in addition to the assurances made to uncompromising service delivery such as education and healthcare, the government of Uganda experience of a devoted civil service has not yielded the projected results of better-quality service delivery or improved confidence between the public and public officers and representatives (Mwesigwa & Oladapo, 2021). Instead, the public has continued to demonstrate frustration with the quality of service delivered at both the central and local government levels by way of mounting community-level demonstrations and violence in the various media platforms (Mwesigwa, 2021:). Analytically, an enormous variance remains visible between the objectives of such strategies and the actual practice.…”
Section: The Policy and Practice Of E-payrollmentioning
confidence: 99%